O tráfico de seres humanos entre as novas formas de criminalidade - Ferracioli, Jéssica (2012)
The work here put forward examines the trafficking of human beings presently, classified as one of the contemporary forms of slavery. Being a phenomenon in evidence, driven by socio-economic disparities, globalization, the flow of people and activities of transnational organized crime, such offense is part of the international agenda, in which its complexity, proportion and rise, renders it one of the new forms of crime. In this moving and rich matter that reaches many areas of the knowledge, two key aspects stand out: the condition of the victim and the criminal-political demands that flow from it, which have prompted international efforts to eradicate it. Thus, the current social model, the conjuncture of human trafficking in the post-modern world as well as the factors that contribute to its increase and the role of organized crime will be briefly examined. Furthermore, this work considers the historical evolution of human trafficking, the historical overview of international instruments, addressing the definition, the constitutive elements and the modalities, including the development of the Brazilian criminal law until the law number 12.015/2009. Thus, the need for efficient criminal protection and the adoption of modern investigation techniques will be emphasized as well as the indispensability of legislative changes in the criminal context, for the current existing legal framework does not provide a satisfactory confrontation with the crime of people trafficking, remaining unaligned with the basic international standards